[AR] Tajalliyyat al-Khitab al-Akhlaqi fi Adab al-Sa’alik wa al-Thawrah ‘ala al-Mujtama’: ‘Urwah bin al-Ward Unmuzajan: Manifestations of Moral Discourse in Tramp Literature and Revolution on Society: ‘Urwah bin al-Ward as an Example (Afaq Lughawiyyah, 2024)
This study aims to deepen the research about tramps literature in order to detect its hidden aspects and to also reveal the human dimension manifested in their poetic discourse.  The vagrancy has been known throughout history by theft and assault. Therefore, this research is an insight into the hidden meaning manifested in the human dimension of each poet. Especially in the pre-Islamic era which has known the beginning and the abundance of Arabic poetry. The focus will be on Orwa Ibn Elward, the leader of the tamps who surpassed Hatim Altaai in generosity and fidelity. In this research, we followed the survey approach of historical facts, events and realities of the tramps, their locations, and the manifestation of their discourse through poetry and their news through literary books.